Porcelain paste for dentistry
By using a combination of cationic surfactant, glass powder and alcohol in dental porcelain paste, the problems of discoloration and reduced transparency after calcination are solved, and the paste is maintained after long-term storage, achieving efficient restoration and good aesthetics of the porcelain.
Patent Information
- Application Number
- CN202380055721.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-25
- Filing Date
- 2023-07-21
- Publication Date
- 2025-03-11
AI Technical Summary
Existing dental porcelain pastes are prone to discoloration after calcination, their transparency is reduced, and they are prone to cure after long-term storage, making it difficult to restore their original state.
A dental porcelain paste containing cationic surfactant (A), glass powder (B) and alcohol (C) is used to adsorb on the surface of the glass powder by cationic surfactant to form hydrophobic particles, avoiding the solidification of the sedimentation layer, and inhibiting carbonization and bubble generation during calcination.
It effectively suppresses discoloration and reduced transparency after calcination, ensures that the porcelain material does not cure after long-term storage, and can easily return to its state when it was just made, maintaining good operability and aesthetics.
Smart Images

Figure BDA0005254009420000161 
Figure BDA0005254009420000171 
Figure BDA0005254009420000181
Abstract
Description
Technical Field
[0001] The present invention relates to a dental porcelain paste. Background Art
[0002] Ceramics have a transparency and color similar to natural teeth, and therefore have become an indispensable material in the production of crowns that require aesthetics.
[0003] Generally speaking, a tooth crown is made by repeatedly filling and calcining a frame (e.g., a metal frame, a ceramic frame) covering a bridge abutment tooth using a dental mixing solution formed by a porcelain material and one or more selected from water and an organic solvent, or a porcelain material obtained by pre-mixing one or more selected from water and an organic solvent with ceramics and making it into a paste.
[0004] Powdered porcelain materials are complicated because they need to be mixed with a solvent each time they are processed, and require proficiency in adjusting the mixing ratio and viscosity according to the desired color tone. However, porcelain materials in paste form are mixed with a solvent in advance to a viscosity that allows dental technicians to work with good workability, and thus the time required for dental technicians to work can be shortened.
[0005] For example, Patent Document 1 discloses a dental paste-like porcelain material comprising a component obtained by dissolving a synthetic and / or natural polymer material having a hydrophilic group in one or more organic solvents selected from diols or triols, ethers having residual hydroxyl groups, and hydroxy(meth)acrylates, and / or water, and discloses a dental paste-like porcelain material that is stable even during long-term storage and is not easily dried / hardened during use.
[0006] In addition, Patent Document 2 discloses the following dental paste material, characterized in that it is made by adding dental porcelain and a solvent, and further adding 0.1 to 20 weight % of inorganic powder with an average particle size of 5 to 50 nm, and discloses that: even if stored for a long time, the dental porcelain does not precipitate and has excellent workability.
[0007] In addition, Patent Document 3 discloses the following dental paste porcelain material, characterized in that it contains glass powder and an organic solvent having a specific boiling point in specific amounts, respectively, and the glass powder contains hydrophobized fine-particle silica having a specific average primary particle size and the particle size is controlled. The following dental porcelain paste is disclosed, which can maintain a paste state for a long time, has excellent coating properties, and hardly causes carbonization and bubbles due to the influence of organic components or polymer components during calcination.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2001-079019
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 3-077804
[0012] Patent Document 3: Japanese Patent Application Publication No. 2020-117499 Summary of the invention
[0013] Problems to be solved by the invention
[0014] However, it is known that the dental paste-like porcelain material described in Patent Document 1 changes color to black or gray during the sintering of the porcelain material, and therefore there is room for improvement in aesthetics.
[0015] In addition, in the dental paste material described in Patent Document 2, the dental paste material is colored by the inorganic fine powder, and there is a concern that the aesthetics may be reduced.
[0016] It is also known that if the dental paste described in Patent Document 3 is stored for a long period of time, the glass powder and the solvent separate, and the solidified sedimentation layer cannot be mixed, making it difficult to reproduce the coating properties immediately after the dental paste is prepared.
[0017] Therefore, an object of the present invention is to provide a dental porcelain paste which can suppress discoloration and reduction in transparency after firing, does not solidify during long-term storage, and can be easily restored to the state immediately after the dental porcelain paste is produced.
[0018] Means used to solve problems
[0019] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by using a dental porcelain paste containing a cationic surfactant (A), a glass powder (B) and an alcohol (C), thereby completing the present invention.
[0020] That is, the present invention includes the following technical solutions.
[0021] [1] A dental porcelain paste comprising a cationic surfactant (A), a glass powder (B) and an alcohol (C).
[0022] [2] The dental porcelain paste according to [1] above, wherein the content of the component (A) is 0.0005 to 2.0 parts by mass based on 100 parts by mass of the component (B).
[0023] [3] The dental porcelain paste according to [1] or [2], wherein the content of component (C) is 20 to 60 parts by mass based on 100 parts by mass of the total of component (B) and component (C).
[0024] [4] The dental porcelain paste according to any one of [1] to [3] above, wherein the total content of component (A), component (B), and component (C) is 75% by mass or more in 100% by mass of the dental porcelain paste.
[0025] [5] The dental porcelain paste according to any one of [1] to [4] above, wherein the component (C) contains a glycol.
[0026] [6] The dental porcelain paste according to any one of [1] to [5] above, wherein the average particle size of component (B) is 1 to 30 μm.
[0027] [7] The dental porcelain paste according to any one of [1] to [6] above, wherein the residual amount of component (A) after strong heating is 8.0% or less.
[0028] Effects of the Invention
[0029] According to the present invention, it is possible to provide a dental porcelain paste which can suppress discoloration and reduction in transparency after firing, does not solidify during long-term storage, and can be easily restored to the state immediately after the dental porcelain paste is produced. DETAILED DESCRIPTION
[0030] Hereinafter, the present invention will be described in detail using embodiments.
[0031] In the present specification, the upper limit and the lower limit of the numerical range (the content of each component, the value calculated from each component, each physical property, etc.) can be combined as appropriate.
[0032] That is, in this specification, the lower limit and upper limit described in stages for the numerical range can be independently combined. For example, based on the description of "preferably 10 to 90, more preferably 30 to 60" for the same item, "preferably the lower limit (10)" and "more preferably the upper limit (60)" can also be combined to "10 to 60".
[0033] In addition, with respect to the numerical range, for example, according to the statement “preferably 10 to 90, more preferably 30 to 60”, the upper limit value may not be particularly limited, and only the lower limit value side may be specified as “above 10” or “above 30”. Similarly, the lower limit value may not be particularly specified, and only the upper limit value side may be specified as “below 90” or “below 60”.
[0034] In addition, unless otherwise specified, when a numerical range is abbreviated as "10 to 90", it means a range of 10 or more and 90 or less.
[0035] Similarly to the above, for example, based on the description of "preferably 10 or more, more preferably 30 or more" and the description of "preferably 90 or less, more preferably 60 or less" for the same item, the "preferable lower limit (10)" and the "more preferably upper limit (60)" may be combined to be "10 or more and 60 or less". Also, similarly to the above, only the lower limit side may be specified as "10 or more" or "30 or more", and similarly, only the upper limit side may be specified as "90 or less" or "60 or less".
[0036] In addition, in this specification, unless otherwise specified, the term "easy recovery" means the property that the dental porcelain paste does not solidify even when the dental porcelain paste is stored for a long time, and can be easily restored to the state just after the dental porcelain paste is made by stirring, etc. Specifically, it means the property evaluated by the method described in the examples.
[0037] In this specification, the term "appearance" refers to "discoloration" and "transparency" when the dental porcelain paste is fired, unless otherwise specified, and specifically refers to properties evaluated by the method described in the Examples.
[0038] [Dental porcelain paste]
[0039] The dental porcelain paste as one embodiment of the present invention contains a cationic surfactant (A) (hereinafter also referred to as “component (A)”), a glass powder (B) (hereinafter also referred to as “component (B)”), and an alcohol (C) (hereinafter also referred to as “component (C)”).
[0040] The dental porcelain paste can exhibit the above-mentioned effects by containing the components (A) to (C). The reason why the effects of the present invention are exhibited is not clear in detail, but it can be considered as follows.
[0041] The hydrophilic group of the cationic surfactant (A) is easily adsorbed to the surface of the glass powder (B) having a high content of silicon dioxide and being negatively charged, and the surface of the glass powder (B) adsorbed with the cationic surfactant (A) is hydrophobized. It is inferred that the hydrophobized glass powder (B) forms an aggregate in which the particles are sparsely distributed in a hydrophilic liquid such as alcohol (C), and therefore, even if a sedimentation layer is generated during long-term storage, the sedimentation layer does not solidify, and when the dental porcelain paste after long-term storage is used again, it can be easily mixed by stirring, etc., and can be restored to the state immediately after the dental porcelain paste is made.
[0042] It can also be inferred that even if the cationic surfactant (A) is adsorbed on the surface of the glass powder (B), it is not bonded. Therefore, after calcination, the organic components derived from the cationic surfactant (A) will not remain on the surface of the glass powder (B), which can inhibit carbonization and the generation of bubbles during calcination, and can inhibit discoloration and reduction in transparency after calcination.
[0043] Hereinafter, each component contained in the dental porcelain paste which is one embodiment of the present invention will be described.
[0044] <Cationic surfactant (A)>
[0045] The cationic surfactant (A) is not limited in type as long as it can exert the effects of the present invention, and examples thereof include ammonium salts having an alkyl group such as alkyl trimethyl ammonium salts, dialkyl dimethyl ammonium salts, alkyl benzyl dimethyl ammonium salts, alkyl ammonium salts, and alkyl pyridinium salts. The alkyl group is preferably an alkyl group having 8 to 18 carbon atoms, and examples of such component (A) include alkyl (8 to 18 carbon atoms) trimethyl ammonium salts, dialkyl (8 to 18 carbon atoms) dimethyl ammonium salts, alkyl (8 to 18 carbon atoms) benzyl dimethyl ammonium salts, or alkyl (8 to 18 carbon atoms) pyridinium salts.
[0046] Among the aforementioned alkyl groups having 8 to 18 carbon atoms, from the viewpoint of easy decomposition, an alkyl group having 8 to 16 carbon atoms is more preferred, and an alkyl group having 8 to 14 carbon atoms is further preferred.
[0047] The component (A) can be used alone or in appropriate combination of two or more.
[0048] The type of cation constituting the salt is not limited, and examples thereof include ammonium ions having an alkyl group such as alkyltrimethylammonium ion, dialkyldimethylammonium ion, alkylbenzyldimethylammonium ion, alkylammonium ion, and alkylpyridinium ion, which can constitute the above-mentioned salt.
[0049] Examples of anions constituting the salt include chloride ions (Cl - ), bromide ion (Br - ) etc. When the cations constituting the salt are the same, the anion is preferably a chloride ion from the viewpoint of ease of decomposition.
[0050] As component (A) formed by the combination of the above anion and cation, suitable examples include chlorides such as cetylpyridinium chloride, lauryltrimethylammonium chloride, dodecylpyridinium chloride, trimethylstearylammonium chloride, dimethylbis(octadecyl)ammonium chloride, benzyldimethyltetradecylammonium chloride; bromides such as lauryltrimethylammonium bromide, trimethylstearylammonium bromide, etc. Among these, at least one selected from cetylpyridinium chloride, lauryltrimethylammonium chloride, dodecylpyridinium chloride and lauryltrimethylammonium bromide is more preferred.
[0051] In addition, from the viewpoint of easy decomposition and easy availability, the above-mentioned chlorides are preferred.
[0052] The component (A) preferably has good decomposability during calcination. The decomposability during calcination can be evaluated, for example, by measuring the intensive heat residue (the residual ratio after calcination at 400° C. for 1 hour).
[0053] The residual amount of component (A) upon strong heat treatment is preferably 8.0% or less, more preferably 5.0% or less, further preferably 1.0% or less, and further preferably 0.5% or less. The residual amount of component (A) upon strong heat treatment can be measured by the method described in the Examples. In other words, in one embodiment of component (A), the residual amount of component (A) upon strong heat treatment is preferably 0.0 to 8.0%, more preferably 0.0 to 5.0%, further preferably 0.0 to 1.0%, and further preferably 0.0 to 0.5%.
[0054] The content of component (A) is preferably 0.0005 to 2.0 parts by mass relative to 100 parts by mass of component (B). When the content of component (A) is 0.0005 parts by mass or more relative to 100 parts by mass of component (B), it is easier to improve the ease of stirring and the ease of restoration even after the dental porcelain paste is stored for a long time, so it is preferred. In addition, when the content of component (A) is 2.0 parts by mass or less relative to 100 parts by mass of component (B), it is easy to suppress the glass discoloration when the dental porcelain paste is calcined, so it is preferred. From this viewpoint, the content of component (A) is more preferably 0.001 to 1.5 parts by mass, more preferably 0.003 to 1.2 parts by mass, more preferably 0.008 to 0.8 parts by mass, more preferably 0.01 to 0.5 parts by mass, and more preferably 0.05 to 0.3 parts by mass relative to 100 parts by mass of component (B).
[0055] In addition, component (A) is more easily thermally decomposed than polymer materials, and even if the added amount is small, as described above, it is easy to obtain the effect that the sedimentation layer generated when the dental porcelain paste is stored for a long time will not solidify. Therefore, it can be inferred that: based on the ease of recovery of the dental porcelain paste after long-term storage, it is also easy to suppress the generation of carbonization and bubbles when the dental porcelain paste is calcined, which can further suppress the degradation of the appearance after calcination. It can be further inferred that: as described above, component (A) is adsorbed to the surface of component (B), but not directly bonded, so after calcination, organic matter derived from component (A) is not easy to remain on the glass surface, which is also a reason that can suppress the degradation of appearance.
[0056] <Glass powder (B)>
[0057] The glass powder (B) is not particularly limited, but is preferably used for dental applications and may contain crystals.
[0058] As the material of glass powder (B), for example, SiO can be listed as glass or crystallized glass as main component (the component with the most content in glass). This glass can also include Al2O3, B2O3, ZnO, K2O, Na2O, Li2O, ZrO2, CaO, MgO, Sb2O3, CeO2, BaO, SnO2, etc., for example, potassium aluminum silicate glass (4SiO2·Al2O3·K2O) selected from amorphous type, potassium aluminum silicate glass, fluoroapatite glass and lithium silicate glass of leucite crystal type can be suitably used at least one. Wherein, more preferably amorphous type potassium aluminum silicate glass. In addition, as aforementioned crystallization, for example, leucite, potassium feldspar, fluorphlogopite, diopside, mica, β-spodumene (LiAlSi2O6), β-calcium metaphosphate, apatite, magnesium titanate, β-eucryptite, aluminum oxide, etc. can be listed.
[0059] In addition, the glass powder (B) may be used alone or in combination of two or more thereof, depending on the application such as metal-baking porcelain, all-ceramic, veneer, etc.
[0060] In addition, the raw materials of the aforementioned glass that become the material of the glass powder (B) can widely use commonly used ceramic raw materials, and various oxides such as SiO2, Al2O3, B2O3, ZnO, K2O, Na2O, Li2O, ZrO2, CaO, MgO, Sb2O3, CeO2, BaO, SnO2, etc. can be used; materials that can form the aforementioned oxides such as SiO2, Al2O3, B2O3, ZnO, K2O, Na2O, Li2O, ZrO2, CaO, MgO, Sb2O3, CeO2, BaO, SnO2 when heated in the atmosphere; or mixtures of the aforementioned oxides and the aforementioned materials that can form the aforementioned oxides when heated in the atmosphere. In this case, the composition of the obtained glass is calculated in advance, and the ratio of each raw material is determined and mixed. The method of mixing the raw materials is not particularly limited, but it is preferably uniformly dispersed.
[0061] The mixed raw materials are heated at about 700° C. or higher. The heating method is not particularly limited as long as all the raw materials are dissolved to form a uniform melt. The method for cooling the melt is also not particularly limited, and air cooling or the like can be used.
[0062] The glass block obtained by the above operation is crushed and classified to prepare a glass powder (B) with an adjusted particle size. The method for crushing and classifying the glass block is not particularly limited. As a crushing device, compression crushers such as jaw crushers and cone crushers can be listed; ball mills such as vibrating ball mills and planetary mills; medium stirring crushers such as tower crushers, stirring trough crushers, and ring crushers; high-speed rotary impact crushers such as pin mills and disc mills; other roller mills; jet crushers; autogenous crushers, etc. As a classification device, screening classifiers such as vibrating screens and sifters can be listed; centrifugal classifiers such as cyclone separators; wet classifiers such as sedimentation classifiers, etc. It should be noted that for these crushing devices or classification devices, in order to avoid the mixing of metal impurities, it is preferred to use a device coated with resin or glass.
[0063] The average particle size of component (B) is preferably 1 to 30 μm, more preferably 2 to 20 μm, and still more preferably 3 to 9 μm. If the average particle size is 1 μm or more, it is easy to suppress the reduction of the transparency of the prosthesis, so it is preferred. In addition, if the average particle size is 30 μm or less, it is easy to improve the restoration ease of the dental porcelain paste, so it is preferred.
[0064] The average particle size of the component (B) refers to a volume-based average particle size (D50) that can be determined by measurement using a laser diffraction scattering method, and can be measured, for example, by the method described in Examples.
[0065] From the viewpoint of being able to calcine at a lower temperature and shortening the calcination time, the glass transition temperature of component (B) is preferably 400-600°C, more preferably 420-580°C, and further preferably 450-550°C. In addition, from the same viewpoint, the softening point of component (B) is preferably 500-680°C, more preferably 520-650°C, and further preferably 550-630°C. In the case where the glass transition temperature is 400°C or above or the softening point is 500°C or above, it is preferred because component (B) can be prevented from dripping during calcination. In addition, in the case where the glass transition temperature is 600°C or below or the softening point is 680°C or below, calcination can be performed at a low temperature, and therefore, deformation of the ceramic frame made of lithium disilicate glass ceramics or the like due to high temperature calcination can be avoided, so it is preferred.
[0066] The linear thermal expansion coefficient (50 to 500°C) of the component (B) can be appropriately selected according to the material of the bridge abutment or the material of the frame, and is not particularly limited, and can be 4.0×10 -6 ~6.0×10 -6 / ℃, for example, it can be 6.1×10 -6 ~13.5×10 -6 / ℃, which can be 6.3×10 -6 ~12.5×10 -6 For example, when a dental porcelain paste is used in a frame containing zirconium oxide as the main component, the linear expansion coefficient of the component (B) is preferably 9.0×10 -6 ~11.0×10 -6 For example, when a dental porcelain paste is used in a frame containing alumina as the main component, the linear expansion coefficient of the component (B) is preferably 6.1×10 -6 ~8.8×10 -6 / °C. The linear thermal expansion coefficient can be measured by, for example, heating a sample from room temperature to 500°C using a thermal analyzer TMA120 (manufactured by Seiko Instruments, with a heating rate of 5°C / min). The linear thermal expansion coefficient can be adjusted using a known method, for example, by adjusting the content of K2O.
[0067] The content of the component (B) is preferably 40 to 80 parts by mass, more preferably 45 to 75 parts by mass, and even more preferably 48 to 72 parts by mass, based on 100 parts by mass of the total of the components (B) and (C).
[0068] <Alcohol (C)>
[0069] Examples of the alcohol (C) include 1,2-ethanediol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,2-pentanediol, 1,5-pentanediol, 2,4-pentanediol, 1,2-hexanediol, 2,5-hexanediol, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol (molecular weight: 200 to 600), propylene glycol, , dipropylene glycol, polypropylene glycol and other straight-chain diol compounds with 2 to 15 carbon atoms; 1-methyl-1,3-propanediol, 2-methyl-1,3-propanediol, 2-methyl-1,4-butanediol, 3-methyl-1,3-butanediol, 2-methyl-2,4-pentanediol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol and other branched diol compounds with 3 to 20 carbon atoms Chain diol compounds; 3-benzyloxy-1,2-propanediol, 4-benzyloxy-1,2-butanediol, methanol, ethanol, 1-propanol, 2-propanol, isopropanol, 1-butanol, 2-butanol, 1-heptanol, 2-heptanol, 3-heptanol, 1-hexanol, 2-hexanol, 3-hexanol, 2-methyl-1-pentanol, 3-methyl-1-pentanol, 4-methyl-1-pentanol, 2-methyl-2-pentanol, 2-methyl-3-pentanol, 2,2- Dimethyl-1-butanol, 2-ethyl-1-butanol, 2-phenoxyethanol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monopropyl ether, dipropylene glycol monoethyl ether, tripropylene glycol monomethyl ether, diethylene glycol monobutyl ether, triethylene glycol monomethyl ether, glycerol, 1,2,3-butanetriol, 1,2,6-hexanetriol.
[0070] The component (C) can be used alone or in appropriate combination of two or more.
[0071] As the component (C), alcohols that are liquid at 20°C are preferred.
[0072] Moreover, the boiling point of component (C) is preferably 100 to 300°C, more preferably 100 to 250°C, and even more preferably 100 to 230°C.
[0073] In addition, component (C) preferably contains a diol, more preferably contains at least one selected from 1,2-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1-methyl-1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 2-methyl-1,4-butylene glycol, 3-methyl-1,3-butylene glycol, 2-methyl-2,4-pentanediol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol and 2-ethyl-1,3-hexanediol, and further preferably contains at least one selected from 1,2-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 3-methyl-1,5-pentanediol and 2-ethyl-1,3-hexanediol.
[0074] The content of the diol in the component (C) is preferably 60 to 100 mass %, more preferably 80 to 100 mass %, further preferably 90 to 100 mass %, and may be 100 mass % in 100 mass % of the total amount of the component (C).
[0075] The content of component (C) is not particularly limited, and is preferably 20 to 60 parts by mass, more preferably 25 to 55 parts by mass, and further preferably 28 to 52 parts by mass, relative to 100 parts by mass of the total of component (B) and component (C). If the aforementioned content of component (C) is 20 parts by mass or more, the kneading properties of component (B) and component (C) are improved, and it is easy to paste, so it is preferred. In addition, if the content of the aforementioned component (C) is 60 parts by mass or less, it is easy to ensure the amount of glass components in the dental porcelain paste, and it is easy to fully carry out porcelain filling, so it is preferred.
[0076] In addition, from the viewpoint of more easily exerting the effect of the present invention, the total content of the component (A), the component (B) and the component (C) in the dental porcelain paste is preferably 75% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and further preferably 95% by mass or more, in 100% by mass of the dental porcelain paste. In other words, in one embodiment of the dental porcelain paste, the total content of the component (A), the component (B) and the component (C) in the dental porcelain paste is preferably 75-100% by mass, more preferably 80-100% by mass, further preferably 90-100% by mass, and further preferably 95-100% by mass in 100% by mass of the dental porcelain paste.
[0077] <Optional Ingredients>
[0078] The dental porcelain paste may further contain other components (optional components) as required, in addition to the components (A) to (C), as long as they do not hinder the effects of the present invention. Examples of such other components include water, colorants, pH adjusters, polymerization accelerators, polymerization initiators, and the like.
[0079] The colorant may be amorphous or crystalline. Examples of the colorant include inorganic pigments, pigments such as opacifying materials, and colorants that discolor when fired.
[0080] Examples of the aforementioned inorganic pigments include praseodymium oxide, vanadium oxide, iron oxide, nickel oxide, chromium oxide, manganese oxide, cerium oxide, tin oxide (e.g., composite oxides containing tin (II) oxide and tin (IV) oxide as components (e.g., vanadium tin yellow, chrome tin red, etc.)), bismuth vanadium yellow, vanadium zirconium yellow, praseodymium yellow, cobalt blue, manganese red, chrome aluminum red, chrome iron zinc, titanium oxide (TiO2), zirconium oxide (ZrO2), etc.
[0081] In addition, examples of the opacifying material include zirconium silicate, tin (IV) oxide, zirconium oxide (ZrO2), zinc oxide, titanium oxide (TiO2), aluminum oxide, etc. These are appropriately contained according to the desired color tone, and when a white color tone is required, 5 to 20% by mass of zirconium silicate is preferably added.
[0082] In addition, examples of coloring agents that discolor during firing include food coloring agents dissolved in organic solvents. Examples of food coloring include organic coloring materials containing two or more aromatic groups, such as Yellow No. 4 (tartrazine), Yellow No. 5 (sunset yellow FCF), Red No. 2 (amaranth), Red No. 102 (new carmine), Blue No. 1 (brilliant blue FCF), Blue No. 2 (indigo carmine), Green No. 3 (fast green FCF), and Red No. 102 (new carmine); organic coloring materials containing condensed aromatic groups with xanthene as a parent nucleus, such as Acid Red 289, bromopyrogallol red, rhodamine B, rhodamine 6G, rhodamine 6GP, rhodamine 3GO, rhodamine 123, eosin, eosin B, eosin Y, fluorescein, and fluorescein isothiocyanate (xanthene-based coloring materials); carmine coloring materials (carminic acid coloring materials); betaine-based coloring materials such as betaine (main components: isobetaine and betanin), betanin, isobetaine, probetanin, and new betanin, and the like.
[0083] Regarding a suitable manufacturing method for a dental porcelain paste as one embodiment of the present invention, a manufacturing method having at least the step of mixing the aforementioned component (A), component (B) and component (C) can be cited. The mixing conditions are not particularly limited, and the contained components can be put in together or divided. The mixed kneading machine can use a common kneading machine. For example, a mortar, a twin-shaft kneading machine (Twinmix), a triple-shaft kneading machine (Trimix), a kneading machine, a planetary agitator, etc. can be cited. Among these, a mortar and a planetary agitator are preferably used.
[0084] In one embodiment of the present invention, the dental porcelain paste preferably contains substantially no photocurable resin. The aforementioned “substantially contains no photocurable resin” specifically means that, in 100% by mass of the dental porcelain paste, the aforementioned photocurable resin is 3% by mass or less, preferably 1% by mass or less, more preferably 0.1% by mass or less, and further preferably 0.05% by mass or less. In other words, in one embodiment of the present invention, the content of the aforementioned photocurable resin is preferably 0 to 3% by mass, more preferably 0 to 1% by mass, further preferably 0 to 0.1% by mass, and further preferably 0 to 0.05% by mass in 100% by mass of the dental porcelain paste. In addition, the dental porcelain paste as one embodiment of the present invention preferably contains no photocurable resin, that is, more preferably 0% by mass.
[0085] The photocurable resin is a resin that is cured by energy rays such as X-rays, ultraviolet rays, and visible light. Examples of the photocurable resin include free radical polymerization type photocurable resins such as urethane acrylate and epoxy acrylate resins, and cationic polymerization type photocurable resins such as epoxy resins.
[0086] In one embodiment of the present invention, the content of the organic polymer material having a hydrophilic group in the dental porcelain paste may be less than 0.5% by mass, may be 0.3% by mass or less, or may be 0.1% by mass or less in 100% by mass of the dental porcelain paste. In other words, in one embodiment of the present invention, the content of the organic polymer material having a hydrophilic group in 100% by mass of the dental porcelain paste may be 0 to 0.5% by mass, may be 0 to 0.3% by mass, or may be 0 to 0.1% by mass.
[0087] The organic polymer material may be, for example, an organic compound having a weight average molecular weight of 1,000 or more. For example, the weight average molecular weight may be a value determined by conversion to standard polystyrene by gel permeation chromatography.
[0088] In addition, as one embodiment of the present invention, the dental porcelain paste only needs to be in the form of a stackable paste when used. Therefore, for example, it can be provided in the form of a dental porcelain kit composed of a liquid component (first agent) containing component (A) and component (C) and a powder component (second agent) containing component (B), and the user mixes the first agent and the second agent immediately before use to prepare the dental porcelain paste. In addition, as another example, a part of component (C) can also be subpackaged. For example, it can be provided in the form of a dental porcelain kit composed of a pre-paste containing component (A), component (B) and a part of component (C) and the remaining component (C), and the user adds the remaining component (C) to the pre-paste immediately before use to prepare the dental porcelain paste for use. In the form of such a kit, the type and content of each component can be appropriately changed according to the above description, and the optional components can be changed by addition, deletion, etc. In addition, when the dental porcelain paste as one embodiment of the present invention is provided in the form of a dental porcelain kit, when used as a dental porcelain paste, it only needs to satisfy the conditions of the dental porcelain paste. For example, at least one of the preparations constituting the kit may already satisfy the conditions of the dental porcelain paste, or the composition of each preparation may be designed in such a way that the conditions of the dental porcelain paste are satisfied only by mixing the preparations.
[0089] [Applications of dental porcelain paste, etc.]
[0090] The dental porcelain paste as one embodiment of the present invention can be used to produce dental prostheses such as ceramic inlays, onlays, veneers, and crowns.
[0091] The frame to be filled with the dental porcelain paste as one embodiment of the present invention is not particularly limited, and examples thereof include a metal frame and a ceramic frame (eg, a zirconia frame).
[0092] The use of the dental porcelain paste is not particularly limited, and the dental porcelain paste can be used as body porcelain (dentine-colored porcelain), neck porcelain, incisal porcelain (enamel-colored porcelain), translucent porcelain, opaque porcelain, dyed porcelain, etc.
[0093] In order to make a dental prosthesis, after filling the dental porcelain paste, calcination is performed. The calcination temperature (maximum calcination temperature) can be appropriately changed according to the type of porcelain, the form of use, etc., and is not particularly limited. It is preferably 700°C or more, more preferably 730°C or more, and more preferably 740°C or more, and preferably 1050°C or less, more preferably 1000°C or less, and more preferably 980°C or less. As described above, the lower limit and upper limit values recorded in these stages can be combined independently. For example, as one mode of the calcination temperature (maximum calcination temperature), it is preferably 700-1050°C, more preferably 730-1000°C, and more preferably 740-980°C. The heating temperature during calcination to the maximum calcination temperature can be appropriately changed according to the type of porcelain, and is not particularly limited. It is preferably 10-70°C / minute, more preferably 15-60°C / minute, and more preferably 20-50°C / minute.
[0094] In addition, before calcining after the dental porcelain paste is stacked, the dental porcelain paste can be dried, and the drying conditions are not particularly limited. Furthermore, from the viewpoint of significantly reducing the bubbles present inside the glass powder (B), the transparency of the resulting dental prosthesis is better, and a better aesthetic can be obtained, the calcination after the dental porcelain paste is stacked can be set as vacuum calcination under vacuum. The vacuum degree in the vacuum calcination is not particularly limited, for example, it can be 750 mmHg or less. The temperature for starting vacuuming is not particularly limited, for example, it can be 550 to 700°C.
[0095] As other embodiments of the present invention, the use of a dental porcelain paste containing component (A), component (B) and component (C) for treating teeth (e.g., aesthetic dental treatment, treatment of defective teeth, prosthetic restoration treatment of artificial teeth, treatment of caries, etc.) can be listed.
[0096] In any of the aforementioned embodiments, the types and contents of the components may be appropriately changed according to the aforementioned description, and optional components may be added, deleted, or otherwise modified. In addition, in any of the aforementioned embodiments, the composition and characteristic values of the dental porcelain pastes may be appropriately changed and combined. Therefore, as long as the dental porcelain pastes can exert the effects of the present invention, one type may be used alone or two or more types may be used in appropriate combination.
[0097] The present invention includes various combinations of the above-described configurations within the scope of the technical concept of the present invention as long as the effects of the present invention are exhibited.
[0098] Example
[0099] Next, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples at all.
[0100] [Examples 1 to 24 and Comparative Examples 1 to 4]
[0101] The dental porcelain pastes of the respective Examples and Comparative Examples were prepared as follows, and their properties were evaluated. The results are shown in Tables 1 to 3 below.
[0102] <Preparation of dental porcelain paste>
[0103] The components described in Tables 1 to 3 below were mixed in a mortar at room temperature for about 10 minutes at the contents (parts by mass) described in Tables 1 to 3 to prepare a dental porcelain paste. The components used are as follows.
[0104] (Cationic surfactant: ingredient (A))
[0105] · Cetylpyridinium chloride monohydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., white solid)
[0106] ·Lauryltrimethylammonium chloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., white solid)
[0107] · Dodecylpyridinium chloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., white solid)
[0108] ·Trimethylstearylammonium chloride (produced by Tokyo Chemical Industry Co., Ltd., white solid)
[0109] ·Dimethylbis(octadecyl)ammonium chloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., white solid)
[0110] Benzyldimethyltetradecylammonium chloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., white solid)
[0111] ·Lauryltrimethylammonium bromide (produced by Tokyo Chemical Industry Co., Ltd., white solid)
[0112] · Trimethylstearylammonium bromide (produced by Tokyo Chemical Industry Co., Ltd., white solid)
[0113] (Glass powder: ingredient (B))
[0114] As for the glass powder, amorphous potassium aluminum silicate glass flakes containing SiO2, Al2O3, ZnO, K2O, Na2O, Li2O, CaO, MgO, Sb2O3, CeO2 and BaO were pulverized with a planetary mill to produce powders with average particle sizes as shown in Tables 1 to 3. As for the average particle size, the volume-based average particle size (D50) was measured by a laser diffraction / scattering method. Microtrac (registered trademark) MT3300II (MICROTRAC BEL) was used as the measuring device, and water was used as the dispersion medium for the measurement.
[0115] (Alcohol: ingredient (C))
[0116] 1,3-Butanediol (manufactured by Kanto Chemical Co., Ltd.)
[0117] 1,2-Propanediol (manufactured by Kanto Chemical Co., Ltd.)
[0118] ·3-Methyl-1,5-pentanediol (manufactured by Kuraray Co., Ltd.)
[0119] 2-Phenoxyethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0120] ·Glycerin (manufactured by Kanto Chemical Co., Ltd.)
[0121] (Additives used instead of cationic surfactants ("other" components in Table 3))
[0122] · Polyethylene glycol monostearate (produced by Tokyo Chemical Industry Co., Ltd., white waxy)
[0123] "AEROSIL (registered trademark) R976S" (manufactured by AEROSIL Japan, hydrophobic fine-particle silica, white powder)
[0124] ·Xanthan gum (Tokyo Chemical Industry Co., Ltd., light yellow solid)
[0125] (Evaluation of the residual amount of surfactant by strong heat treatment)
[0126] 0.3 g of the above-mentioned cationic surfactant, polyethylene glycol monostearate or xanthan gum was weighed into a crucible, respectively, and placed in an electric furnace, and heated to 400°C at a heating rate of 20°C / min, and maintained and heated at 400°C for 1 hour. The heating was performed in the electric furnace under atmospheric conditions. The weight of the residual amount obtained after heating was measured, and the strong heating residual amount was calculated according to the following calculation formula.
[0127] In addition, it was evaluated that the decomposition point of the surfactant having a strong heat residual amount of 0.5% or less was 400° C. or less. It is to be noted that the decomposition point of the cationic surfactant is preferably 400° C. or less.
[0128] In Comparative Examples 2 and 4, the residual amount of additives used instead of the cationic surfactant was also evaluated in the same manner.
[0129] · Residual weight after intensive heating (mass %) = {(weight of sample after heating at 400°C for 1 hour [g]) / (weight of sample before heating [g])}×100
[0130] ※ Sample weight before heating = 0.3g
[0131] <Evaluation of dental porcelain paste>
[0132] (1) Evaluation of recovery after long-term standing
[0133] 10 g of the dental porcelain paste prepared in the above-mentioned Examples and Comparative Examples was weighed into a 20 mL container and allowed to stand in a thermostatic chamber at 60° C. for two weeks to prepare a test body. After standing for two weeks, the test body was cooled to 23° C. and manually stirred with a stainless steel spatula until it returned to the state of the prepared paste before standing. The time and effort required for stirring were evaluated according to the following criteria.
[0134] <Evaluation Criteria>
[0135] A: The stainless steel spatula easily penetrates into the test body, and the test body returns to the state before standing within 1 minute after the start of stirring.
[0136] B: The stainless steel spatula was inserted into the test body and the test body returned to the state before standing within 1 minute and within 3 minutes after the start of stirring.
[0137] C: The stainless steel spatula was difficult to penetrate into the test body, and the test body returned to the state before standing within 3 minutes and 10 minutes after the start of stirring.
[0138] D: Solidified to the extent that a stainless steel spatula could not penetrate the test body, and even if stirring was continued for more than 10 minutes after the start of stirring, the solidification could not be eliminated and the state before standing was not restored.
[0139] (2) Appearance evaluation after calcination
[0140] A sample obtained by applying the dental porcelain paste prepared in the aforementioned embodiments and comparative examples to a thickness of 0.2 mm on a zirconia plate of 10 mm in length and 35 mm in width, and a sample obtained by applying the dental porcelain paste to a thickness of 1.0 mm were prepared, and vacuum calcined at the temperatures listed in Tables 1 to 3 to obtain sintered bodies.
[0141] The appearance of each obtained sintered body was visually observed and evaluated according to the following criteria (N=3).
[0142] <Evaluation Criteria>
[0143] A: The 0.2mm thick and 1.0mm thick sintered bodies are both glass and do not change color, but are transparent.
[0144] B: In the 0.2 mm thick sintered body, the glass did not change color and had a sense of transparency, but in the 1.0 mm thick sintered body, the glass turned gray and a decrease in transparency was observed.
[0145] C: In both the 0.2 mm thick and 1.0 mm thick sintered bodies, the glass turned gray, and a decrease in transparency was observed.
[0146]
[0147]
[0148] [Table 3]
[0149]
[0150] (*1): Content relative to 100 parts by mass of component (B).
[0151] The results in Tables 1 and 2 show that the dental porcelain pastes of Examples 1 to 24 containing components (A) to (C) do not solidify in the sedimentation layer produced during long-term storage, and when the dental porcelain pastes after long-term storage are used again, they can be easily restored to the state immediately after the dental porcelain pastes are made. It is also known that the deterioration of the appearance during firing can be suppressed.
[0152] On the other hand, the results in Table 3 show that the dental porcelain paste of Comparative Example 1 not containing the component (A) solidified during long-term storage, could not be released by stirring with a spatula, and could not be restored to the state before storage.
[0153] It is also found that the dental porcelain pastes of Comparative Examples 2 and 3 containing polyethylene glycol monostearate or hydrophobic fine-particle silica instead of component (A) also solidify during long-term storage and cannot be desolidified by stirring with a spatula, and cannot be restored to the state before storage.
[0154] It is also found that the dental porcelain paste of Comparative Example 4, which contains xanthan gum instead of component (A), has a significantly lower appearance after firing. This is presumably because xanthan gum, a polymer compound, is not completely burned off.
[0155] Industrial Applicability
[0156] The dental porcelain paste of the present invention can suppress the deterioration of the appearance during firing, and is also excellent in the ease of restoration during long-term storage.
[0157] Furthermore, the dental porcelain paste of the present invention is excellent in ease of restoration after long-term storage, so that suitable operability can be reproduced by manual work of dental technicians. In addition, the appearance degradation during calcination can be suppressed, so the color tone can be accurately adjusted.
[0158] Therefore, the dental porcelain paste of the present invention can be used for prosthetic restorations of artificial teeth having aesthetics close to natural teeth, and can be suitably used as a dental porcelain paste that can be suitably used even after long-term storage when filling is performed manually by a dental technician.
[0159] In addition, in particular, with the increasing demand for ceramic crowns and the improvement of personal aesthetic requirements, it is expected that the frequency of use of dental ceramics will increase, and therefore, the dental ceramic paste of the present invention is useful.
Claims
1. A dental porcelain paste comprising a cationic surfactant (A), a glass powder (B) and an alcohol (C).
2. The dental porcelain paste according to claim 1, wherein: The content of the component (A) is 0.0005 to 2.0 parts by mass based on 100 parts by mass of the component (B).
3. The dental porcelain paste according to claim 1 or 2, wherein: The content of the component (C) is 20 to 60 parts by mass based on 100 parts by mass of the total of the component (B) and the component (C).
4. The dental porcelain paste according to any one of claims 1 to 3, wherein The total content of the component (A), the component (B) and the component (C) is 75% by mass or more in 100% by mass of the dental porcelain paste.
5. The dental porcelain paste according to any one of claims 1 to 4, wherein Component (C) contains a diol.
6. The dental porcelain paste according to any one of claims 1 to 5, wherein The average particle size of the component (B) is 1 to 30 μm.
7. The dental porcelain paste according to any one of claims 1 to 6, wherein The heat residual amount of the component (A) is 8.0% or less.
Citation Information
Patent Citations
Dental pasty material
JP1991077804A
Paste-form porcelain for dental treatment
JP2001079019A
Dental porcelain paste with excellent coating properties
JP2020117499A